2018
DOI: 10.1093/petrology/egy073
|View full text |Cite
|
Sign up to set email alerts
|

Linking In Situ Crystallization and Magma Replenishment via Sill Intrusion in the Rum Western Layered Intrusion, NW Scotland

Abstract: The construction of layered mafic-ultramafic intrusions has traditionally been attributed to gravitydriven accumulation, involving the mechanical settling of crystals onto the magma chamber floor, at the interface between the crystal mush at the base and overlying replenishing magma, such that the layered sequence of cumulates (i.e., the crystal mush) at the floor aggrades upwards. The Rum Western Layered Intrusion (WLI) is a ~250 m sequence of layered peridotite cumulates comprising the structurally lowest po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 103 publications
2
11
0
Order By: Relevance
“…Hepworth et al (2017) showed that harrisite layers found in the Unit 10 peridotite represent sills based largely on their topology. For example, they highlighted the presence of small-scale features such as upward-oriented apophyses, bifurcation, and lateral discontinuities, which must have formed within the crystal mush and not upon the magma chamber floor (see also Donaldson 1982;Hepworth et al 2018). The harrisite layers found throughout the welllayered peridotites in this study display the same features as those described in the Unit 10 peridotite ( Fig.…”
Section: Incremental Emplacement Of Peridotite Sillssupporting
confidence: 57%
See 4 more Smart Citations
“…Hepworth et al (2017) showed that harrisite layers found in the Unit 10 peridotite represent sills based largely on their topology. For example, they highlighted the presence of small-scale features such as upward-oriented apophyses, bifurcation, and lateral discontinuities, which must have formed within the crystal mush and not upon the magma chamber floor (see also Donaldson 1982;Hepworth et al 2018). The harrisite layers found throughout the welllayered peridotites in this study display the same features as those described in the Unit 10 peridotite ( Fig.…”
Section: Incremental Emplacement Of Peridotite Sillssupporting
confidence: 57%
“…A recent investigation of the Unit 10 peridotite by Hepworth et al (2017) supported an intrusive origin for this body, and showed that much of the peridotite was formed incrementally, via the intrusion of numerous thin sills (represented by harrisite layers). A similar interpretation was applied to the WLI (Hepworth et al 2018). Despite the lack of layer continuity typical of sills in the ELI and WLI, intrusive peridotite is likely a major component of the CI (Volker and Upton 1990), contrary to the classic model (e.g.…”
Section: Geological Backgroundmentioning
confidence: 96%
See 3 more Smart Citations